Jaringan Yahudi internasional di Nusantara - Artawijaya, 1979- (Jakarta : Pustaka Al-Kautsar, 2010)
History of Freemasonry and network of Jewish people in Indonesia.
Includes bibliographical references (p. 277-293).
Keywords: Freemasonry -- Indonesia -- History; Jews -- Indonesia -- History